Multisequence Quantitative Magnetic Resonance Neurography of Brachial and Lumbosacral Plexus in Chronic Inflammatory Demyelinating Polyneuropathy - Su, Xiaoyun; Kong, Xiangquan; Alwalid, Osamah; Wang, Jing; Zhang, Huiting; Lu, Zuneng; Zheng, Chuansheng (Frontiers in Neuroscience, 2021)
Background and purpose: Chronic inflammatory demyelinating polyneuropathy (CIDP) is an uncommon demyelinating disorder. Although treatable, it is difficult to diagnose. The purpose of this study was to evaluate diagnostic performance and abnormalities of plexus via quantitative multisequence magnetic resonance neurography (MRN) for CIDP. Methods: Brachial and lumbosacral (LS) plexus of 37 CIDP patients and 37 age and gender-matched controls were examined by using multisequence MRN. Nerve diameter, nerve-to-muscle T2 signal intensity ratio (nT2), contrast-enhanced ratio (CR), fractional anisotropy (FA) and apparent diffusion coefficient (ADC) were determined in both plexus, and tractographies were performed. The disease histories and the Inflammatory Rasch-built Overall Disability Scale (I-RODS) questionnaire scores were documented before MRI scans. Results: The sizes of nerve roots were larger in CIDP (P< .01). CR, nT2 and ADC were significant higher, while FA was lower in CIDP than in controls (P< .01). FA had the highest sensitivity (.809) and area under the curve (AUC) (.925), while the highest specificity was .961 for CR in single-parameter. The combination of FA and CR have the highest sensitivity, specificity, accuracy and AUC in the LS plexus. CR only had a weak correlation with nT2 (P< .05). ADC and diameter had positive correlation with nT2, and the diameter and nT2 had negative correlation with FA in CIDP (P< .05). FA had a negative correlation with the duration in the CIDP (r’s= -.404, P<.05). No significant correlation between the I-RODS scores and MR multi-parameters (P<.05). Conclusion: Multisequence MRN possesses high diagnostic performance in the LS plexus. Sampling perfection with application-optimized contrasts using different flip angle evolution (SPACE) combined with DTI and contrast enhancement serve as a recommended composite protocol for CIDP.